Evolution of carbon capture and storage by mineral carbonation: Data analysis and relevance of the theme - Galina, Natália Ribeiro [UNESP]; Arce, Gretta L.A.F. [UNESP]; Ávila, Ivonete [UNESP] (Elsevier, 2019)
Mineral carbonation has enormous potential for carbon capture and storage (CCS). CO2 is a greenhouse gas that can be converted into environmentally stable products through mineral carbonation, which has been pointed out as the most promising technology to reduce CO2 emissions and environmental impacts generated therefrom. Thus, this study presents an overview of the state of the art in terms of mineral carbonation research conducted between 2002 and 2018 with the aim of analyzing its evolution so as to identify the main scientific challenges in literature to indicate future research on it. The results reveal an increase in the number of publications and citations during the period under study and that there has been a fivefold increase in publications and citations on average in the latest five years. The analyzed works have made use of different kinds of industrial waste as raw material for mineral carbonation, whose most widely studied products were mining waste, Coal fly ash and Steelmaking slag. Mining waste is the most commonly studied material, which presents the greatest potential for mineral carbonation. Analyzes of recent articles have revealed that many challenges are yet to be overcome, such as the deployment of industrial carbonation technologies, mostly those that increase the efficiency of converting CO2 into carbonates and reduce its overall budget. Thus, further studies are needed with the aim of increasing the process reaction rate, reducing the use of chemical reagents and defining the mineralogical characteristics of raw materials in order to determine an ideal raw material for carbonation processes and analyze the market and profitability of products generated through mineral carbonation.
Keywords: Carbon capture; CCS; Mineral carbonation; Mineralization